New Zealand’s Policing Efforts in the Pacific: Gender Programs, Practices, and Performances - Stewart-Withers, Rochelle (Journal of contemporary criminal justice, 2022)
Research increasingly identifies gender equality as being vital for the achievement of lasting peace and prosperity. New Zealand Police have delivered a range of capacity-building projects and programs in Pacific Island countries over many years. In this article, we examine the gendered impact of two such programs and consider how they have been delivered by New Zealand’s police officers. Although specific gender-focused programs helpfully prioritize gender, they can also unhelpfully create silos; however, gender-focused programs are likely to be most impactful when combined with certain practices and performances of gender. Drawing on observational research, we suggest that some male police personnel operating in communities may have significant gendered impacts by role modeling a form of “caring masculinities.” The demonstration of caring values by men potentially constitutes a vital contribution toward achieving deeper and broader structural change in the gender space. Practices and performances of gender should be elevated and evaluated alongside targeted program goals.